Understanding the evolution of environmental and energy performance of the US corn ethanol industry: evaluation of selected metrics. (10th October 2013) - Chum, Helena L.; Zhang, Yimin; Hill, Jason; Tiffany, Douglas G.; Morey, R. Vance; Goss Eng, Alison; Haq, Zia
Abstract Throughout the past two decades, numerous studies characterized the greenhouse gas (GHG) emissions and net energy balance of corn ethanol production in the USA. A wide range of reported values resulted from differences in the vintage of the data used to evaluate the ethanol conversion technology and the agricultural practices of corn production, which evolved substantially during the rapid growth phase of the industry. Methodological differences in life cycle assessments also caused the reported values to vary widely. With corn dry mills growing from 30% of total installed ethanol production capacity in 1990 to 80–90% from 2006 to 2011, we document the evolution of this industry using vintage‐specific data to analyze selected energy and environmental metrics, including GHG emissions, fossil energy use, direct land use, and GHG emissions reduction per hectare of land harvested for ethanol production. Our estimates indicate that production and use of corn ethanol emitted 44% fewer GHG emissions, consumed 54% less fossil energy and required 44% less land in 2010 compared to 1990 (on a life cycle basis). Our review and analysis point to strategies for reducing the carbon footprint of the corn dry mill industry by building on the progress already achieved. Using biomass (e.g. residues from corn production) for process heat or combined heat and power is one such strategy. Additional environmental benefits are projected from the adoption of integrated gasification combined cycle technology (using corn residues), which leads to energy‐self‐sufficient mills or net electricity producers depending on the power system configuration. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd